Intervening with laughter: using laughter/humor to create positive experiences in dementia relationships - Matter, Michelle M., author; Faw, Meara H., advisor; Knobloch, Katherine R., committee member; Long, Ziyu, committee member; Lucas-Thompson, Rachel G., committee member (Colorado State University. Libraries, 2024)
Humor and laughter have various positive outcomes on people's health and relationships both within healthcare settings and in daily life. In particular, humor and laughter can be beneficial for individuals impacted by dementia. This dissertation project was an engaged, mixed methodological intervention in which a program containing humor activities was created for people with dementia and their care partners to determine whether actively engaging with humor and laughter would be associated with positive outcomes for participants' well-being, observed behaviors, and relationships. Data collection methods included real-time observations as well as pre- and post-test surveys. Results indicated that participants were able and willing to participate in the program, that they engaged in various relational maintenance strategies during the program, and that the program was enjoyable and effective at creating positive personal and interpersonal outcomes for participating dyads. This project contributes to the scholarly community by investigating the usefulness of a noninvasive intervention within an understudied dyadic and aging population while demonstrating the powerful outcomes that can result from engaged scholarship and community collaborations. Additionally, this work offers the community partner a "plug-and-play" program that can be repeated in the future and provided participants with valuable and enjoyable experiences.
Keywords: dementia; interpersonal communication; relational maintenance; humor; community-engaged research; laughter